The effect of sensory processing on the work performance of call centre agents in a South African context - Lombard, Annemarie (Department of Health and Rehabilitation Sciences, 2015)
Background: Call centres are thriving and expanding commercial enterprises providing cost-effective ways for organisations to connect with new and existing clients through telecommunication channels. Call centre agents perform this function telephonically for 75% of the day in large open-plan office environments characterised by workloads that are demanding, repetitive and highly scripted. Verbal abuse by clients is prevalent adding to a work experience that is potentially emotionally draining and stressful. Agents are under constant surveillance and monitoring to abide with commercial regulations but also to ensure high call volume and quality engagement with clients, these being the most important performance indicators. High staff absenteeism and attrition levels account for large financial losses in the industry. To date no studies have been found considering the impact of sensory processing of call centre agents on their performance, absenteeism and attrition. Sensory processing considers the neuro-physiological and behavioural components of individuals in the interactions with their daily work occupations and life environments. Although predominantly applied in paediatric clinical populations in occupational therapy, sensory processing provides universal truths about human behaviour which can add value to promoting wellness amongst healthy adults in work environments. Design: A quantitative, non-experimental and correlational study design was used to measure and compare demographic, sensory processing and performance data from 459 call centre staff within four fully operational call centres, which varied in type of operation, employer and geographical area in South Africa. The standardised and validated 60-item Adolescent/Adult Sensory Profile (Brown, Tollefson, Dunn, Cromwell & Fillion, 2001) was used to measure sensory processing as neurological thresholds and potential propensity for individuals to cope with high sensory stimulating work environments. Agent performance data in each of the four centres were recorded daily, in real time, using sophisticated information technology systems, and included details about absenteeism. Attrition data were collected after the initial data intake to reflect true attrition. Results: Data were analysed using statistical methods to obtain locality (e.g. means, medians), dispersion (e.g. standard deviations and interquartile ranges) and associations (e.g. Spearman Rank correlations). Results showed strong, consistent and significant correlations between agents who displayed sensation avoiding processing and poor performance. Agents who exhibited sensation seeking processing had higher performance ratings. To a lesser, yet still significant, degree agents with low registration and sensory sensitivity also had lower performance ratings. Sensory sensitive agents were absent less often than other workers and sensation seeking agents showed a tendency for higher attrition. Results differed between service inbound call centres to sales and collections outbound ones. Team leaders, who are high performing agents promoted into these positions, had less sensory sensitive and sensation avoiding processing styles. A novel subset structure was designed to account for the multidimensional capacity of the AASP, and this was correlated with all the performance data. It provided a preliminary method for use in further research studies. The study strengths were the innovative sample in measuring sensory processing of healthy populations at work and the compilation of performance data through sophisticated computerised systems, which minimised the margin of error. Study limitations were the use of a self-questionnaire format for profile data collection and small sample sizes in subsequent data collection stages. Recommendations: The AASP has the potential to be used by call centre human resource practitioners for recruitment and performance management. Improved sensory environmental considerations and adaptations supportive of a more successful and healthier agent-job-environment fit are provided. The study findings support knowledge transfer into other general human resource management, education and training, occupational health management and occupational therapy practises. It expands the application of sensory processing theories and informs future research.